TECHNICAL EFFICIENCY PERFORMANCE OF CONVENTIONAL BANKS - Endri Endri (Universitas Gunadarma, 2012)
This study aims to measure the performance of the technical efficiency of the conventional commercial banks during the period 2008-2009 by using non-parametric method of Data Envelopment Analysis (DEA). Test results showed that the total of all conventional commercial banks during the period 2008-2009 has not shown that optimal performance in which the level of technical efficiency is still below 100 percent. Appalling conditions, the efficiency of national banks experienced a decline of 73.50% in 2008 fell to 69.61% in 2009. With the advantages possessed in the management of banks, foreign-owned banks generate higher performance efficiency than domestically owned banks. For the whole bank, in 2008 there were 97 banks that have the performance of inefficiency and down to 96 banks in 2009.Key Words: bank efficiency, DEA, bank size, domestic bank, foreign bank